Psychosocial risk factors and psychological distress in Peruvian workers - Tenorio Castillo, Victoria Rocio (2024)
This study aimed to analyze the association between psychosocial risk factors and psychological distress in Peruvian employees during the year 2023. A total of 201 workers participated. The study has a quantitative, basic type approach, with an empirical design, associative strategy, explanatory. The CoPsoq-istas21 Questionnaire in its version 1.5 (Moncada et al., 2014) and the Kessler Psychological Distress Scale - K10 Questionnaire (Brenlla & Aranguren, 2010) were used. In an approach to the data with structural equation modeling, it was found that the model composed of the six psychosocial risk factors explains psychological distress by 30 %. Furthermore, this model demonstrates a good fit (CFI=.946; TLI=937; RSMEA=.040; SRMR=.049), with self-esteem (β=-.27; p=.009<.05) and work-life balance (β=.13; p=.035<.05) maintaining statistically significant associations with psychological distress. On the other hand, it is women who show a greater impact compared to men in psychological demands (rbis=.281; p=004), social networks, social support, and quality of leadership (rbis=.29; p=.003), and self-esteem (rbis=.324; p<.001). In conclusion, the psychosocial risk factors of esteem and double presence explain psychological distress. Additionally, women exhibit greater psychosocial risk in terms of psychological demands, social networks, social support, and the quality of leadership and esteem.